Newly Discovered Lexical Items in Documents of Armenian Community of Kamieniec (16th-17th Centuries) - G. K. Khachatryan (Научный диалог, 2025)
This article investigates the lexical characteristics of the chronicle of the Armenian community that settled in the medieval Polish town of Kamieniec during the 16th and 17th centuries. The study draws on over fifteen lexical items that have not been previously examined by specialists in Middle Armenian. The results of the comparative analysis reveal that the majority of these words are direct borrowings from Polish, Ukrainian, German, and Kipchak languages. Additionally, there are some indirect borrowings from Latin. It is reported that a portion of the newly discovered words constitutes neologisms created based on typical word formation patterns of Middle Armenian. For the first time, this article explores and introduces into academic discourse data on the newly identified lexical units of Polish Armenians from the 16th to 17th centuries, which will enrich the layers of borrowings and neologisms in Middle Armenian. The study emphasizes that the Armenians of Kamieniec, while cohabitating with Poles, Ukrainians, and Kipchaks, engaged in financial-economic, legal, cultural, and other interactions, resorting to borrowings when necessary. This underscores their complete adaptation and integration into this environment.